FAW-Volkswagen Audi : pioneering the future (2012-present) - McFarlan, F. Warren (SAGE Knowledge. Cases., 2016)
The FAW-Volkswagen Audi "trilogy" case describes Audi's development history in China and the problems it faces currently, as well as demonstrating the strategies employed by FAW-Volkswagen Audi in their thirty year business partnership. The third case in the series describes how FAW-Volkswagen Audi responded to the decrease in the demand for luxury cars as the market matured and became stable.